Spatial Pattern of Rural Settlement System in Eastern Uttar Pradesh - Siddiqui, Shamsul H.; Usmani, Tariq M. (National Geographical Journal of India, 2022)
Settlements, which are concrete expression of human occupation of the earth surface, have always engaged the attention of geographers. The accounts of early travelers and explorers as well as the ancient books of religion and philosophy contain myriads of such references where settlements have occupied prominent place along with features of physical landscape. An attempt has been made here to analyze the spatial distribution of rural settlements according to their size. The size of settlements helps to identify the population threshold of social amenity, which is an important aspect of locations studies as human settlements produce a certain degree of order in their distributional pattern over the space and this in some way reflects the functional relations among centers.